A Small Robotic Step for the Therapeutic Treatment of Mental Illnesses: First Round - Martínez, Carlos (2020)
The advances in psychological therapies to treat mental illnesses have been of vital importance in recent times, especially by the combination with technology. Appealing to new mechanisms gives some hope of improvement in treatments and patients. In this work we show the ease in the development of routines that can help the quality of life of people suffering from Alzheimer’s and autism, diseases that lend themselves to the programming of routines related to the daily life of patients. The routines developed by students of psycho-pedagogy and documented by our work team are waiting for being applied in case studies in future works. The general conclusion of the assignment is the concentration that arose having to use a robot as part of therapy routines and the quest for information to combine new technologies with psychology. The assignment can be considered as impressive because working with a robot awakens positive emotions in those who are developing robotic therapies.